Gestational Bisphenol A Exposure Impacts Embryonic Hypothalamic Microglia Numbers, Ramification, and Phagocytic Cups - Rosin, Jessica M.; Tretiakov, Nikol; Hanniman, Emily; Hampton, Kiana; Kurrasch, Deborah M. (Frontiers in Neuroscience, 2022)
Microglia are a resident population of phagocytic immune cells that reside within the CNS. During gestation, they are highly sensitive to their surrounding environment and can alter their physiology to respond to perceived neural insults, potentially leading to adverse influences on nearby neural progenitors. Given that bisphenol A (BPA) itself can impact developing brains, and that microglia express estrogen receptors to which BPA can bind, here we asked whether fetal microglia are responsive to gestational BPA exposure. Accordingly, we exposed pregnant dams to control or 50 mg/kg BPA-laced chow during gestation to investigate the impact of BPA on embryonic hypothalamic microglia. Gestational BPA exposure from embryonic day 0.5 (E0.5) to E15.5 resulted in a significant increase in the number of microglia present in the hypothalamus of both male and female embryos. Staining for microglial activation using CD68 showed no change between control and prenatal BPA-exposed microglia, regardless of sex. Similarly, analysis of cultured embryonic brains demonstrated that gestational BPA exposure failed to change the secretion of cytokines or chemokines, regardless of embryo sex or the dose (50 g/kg or 50 mg/kg) of BPA treatment. In contrast, live-cell imaging of microglia dynamics in E15.5 control and gestationally-exposed BPA hypothalamic slices showed increased ramification of microglia exposed to BPA. Moreover, live-cell imaging also revealed a significant increase in the number of microglial phagocytic cups following exposure to gestational BPA. Together, these results suggest that gestational BPA exposure impacts embryonic hypothalamic microglia, perhaps leading them to alter their interactions with developing neural programs.